Legal Protection Regarding the Absentee Sale and Purchase of Agricultural Land in Pekalongan City, Central Java - Aditya, Agung; Wibowo, Dwi Edi; Prematura, Aditya Migi; Yazid, Ahmad (Law Research Review Quarterly, 2025)
The objective of this study is to examine and analyze the considerations used by the Land Office of Pekalongan City in rejecting applications for the transfer of ownership rights over agricultural land in Pekalongan City, Central Java. Additionally, this study aims to explore and analyze the resolution of issues related to the sale and purchase of agricultural land that do not meet the minimum land area requirements stipulated by law. This research adopts a descriptive approach with an empirical juridical method. The study involves library research to obtain secondary data through document analysis, while field research is conducted to gather primary data through interviews with research subjects using structured interview guidelines. The analysis employed in this study is qualitative and presented descriptively. Based on the anticipated findings, the author expects that the considerations used by the National Land Office include the following: first, the land is being purchased by a buyer who resides outside the subdistrict where the agricultural land is located, with a distance of approximately nine kilometers between the land and the buyer’s residence. The second consideration pertains to the land size, as the object of the sale measures less than two hectares. To address these issues, buyers may pursue several resolution strategies. One approach is to designate one among them as the sole owner or transfer ownership to another party, in accordance with Article 9(2) of Law No. 56 Prp of 1960. Another possible solution is land conversion through drainage, as the land in question does not fall within a designated green area.